PENGARUH KUALITAS PRODUK, KUALITAS PELAYANAN DAN KEPUASAN PELANGGAN TERHADAP LOYALITAS PELANGGAN MOTOR YAMAHA KECAMATAN SEKUPANG KOTA BATAM - Wasiman Wasiman (Yayasan Akrab Pekanbaru, 2018)
The purpose of this study is to determine the effect of Product Quality, Service Quality and customer satisfaction on customer loyalty Yamaha Motor located in the District Sekupang Batam City. This study used three independent variables, namely Product Quality (X1) Quality of Service (X2) and customer satisfaction (X3) with customer loyalty as dependent variable. The population used in this study 150 was calculated using the slovin formula. Methods of data analysis using multiple linear data analysis. The result of R square test of dependent variable can be explained by independent variable that is Product Quality, Service Quality and customer satisfaction equal to 74,8% and rest 25,2% influenced by other factor outside this research. Keywords: Service Quality, Customer Satisfaction, Loyalty Customers